(untitled) (Fiep Bulletin - online, 2016)
Introduction: the Pilates Method is gaining more space in the treatment of musculoskeletal disorders, including changes in the lumbar spine that can cause back pain. Objective: literature review on the effectiveness of the Pilates method in the treatment of low back pain.Method: scientific articles were searched in electronic databases Lilacs and SciELO, published between 2009 and 2014, using as criteria for inclusion studies directed to the treatment of low back pain by Pilates. Results: four studies were selected for analysis, which demonstrates that Pilates can be practiced by different populations and with different purposes, restoring the function of the spine and preventing the rise of low back pain. Conclusion: although further studies are necessary, there is scientific evidence that the Pilates method is effective in the treatment and prevention of low back pain.